2018
DOI: 10.1177/0255761418771992
|View full text |Cite
|
Sign up to set email alerts
|

QR codes for instrumental performance in the music classroom

Abstract: This article presents an experiment with a group of secondary school music students in Spain. We used music score sheets enriched with Quick Response codes as a resource for the practice required to play a musical instrument. The first group (n = 56) was compared with another group (n = 56) that used traditional resources (textbooks and compact discs). The results of the research supported the fact that the students who used QR codes associated with videos – read by using mobile devices such as smartphones or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
1
2
0
2
Order By: Relevance
“…As part of mobile learning, QR-Codes give boxers the ability to link printed scientific materials in the Boxer’s Guidebook to AR digital educational resources via a smartphone connected to the Internet, making it easy to access digital educational resources and to display them according to the educational process. This is in line with the findings of studies by Chung et al [ 69 ], Palazón and Giráldez [ 68 ], and Traser et al [ 67 ], which indicated that QR codes could bridge the gap between printed and multimedia educational resources in education, thereby improving learning outcomes, learning effectiveness, and learners’ attitudes toward learning.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As part of mobile learning, QR-Codes give boxers the ability to link printed scientific materials in the Boxer’s Guidebook to AR digital educational resources via a smartphone connected to the Internet, making it easy to access digital educational resources and to display them according to the educational process. This is in line with the findings of studies by Chung et al [ 69 ], Palazón and Giráldez [ 68 ], and Traser et al [ 67 ], which indicated that QR codes could bridge the gap between printed and multimedia educational resources in education, thereby improving learning outcomes, learning effectiveness, and learners’ attitudes toward learning.…”
Section: Discussionsupporting
confidence: 90%
“…According to a number of studies [67][68][69], QR codes are an effective tool for bridging the gap between printed and multi-media educational resources in formal education, as well as improving learning outcomes, learning effectiveness, and learners' attitudes toward education.…”
Section: Plos Onementioning
confidence: 99%
“…In the context of Internet+, the threshold of learning vocal music is slowly lowered, and as long as one has a computer or a smartphone that can be connected to the Internet, one can freely search for the vocal music courses they need and thus study independently [14]. Some vocal students in general institutions are no longer restricted by the strength of teachers and their teaching staff, and they can search for the online vocal teaching resources they need through the Internet for independent learning [15][16].…”
Section: Research Backgroundmentioning
confidence: 99%
“…Somos conscientes del "vértigo pedagógico" que puede producir la eliminación del libro de texto en la planificación didáctica de los docentes, pero el aula de música del siglo XXI tiene al alcance infinidad de recursos digitales que, como bien indican numerosos autores (Debevc et al, 2020;Lorenzo-Quiles et al, 2015;Nijs, 2018;Palazón & Giráldez, 2018;Wan & Gregory, 2018), mejoran el rendimiento académico de los estudiantes en música. Por otro lado, la presencia cada vez mayor de Sistemas Digitales Interactivos (SDI) aminora, por no decir que elimina casi por completo, las dificultades que puede generar la visualización por parte del alumnado de partituras, textos de canciones, musicogramas… o la difícil tarea que supone para el profesorado la representación gráfica de los mismos en la pizarra.…”
Section: Discusión Y Conclusionesunclassified